Characterise to manage: first analysis of small-scale fishery profiles on the Amazon coast - Carneiro, Manoela de Almeida; Prestes, Luiza; Suárez-Ahumada, Benjamín; Barthem, Ronaldo Borges; Costa, Dimitri de Araújo (Frontiers in Marine Science, 2025)
Artisanal fishing along the coast of Pará (Eastern Amazon) plays a vital role in generating local income and supplying fish to a broad consumer market. Small-scale fisheries employ diverse strategies, with gillnets being the predominant and most productive gear. Fishers are not homogeneous in their practices and can be classified as specialists, focusing on particular fishing areas, target species, or capture methods, or as generalists, displaying greater flexibility and sometimes engaging in non-fishing activities. This study characterises the strategies of small-scale artisanal fishers in the Eastern Amazon based on distinct fishing profiles. To address the high heterogeneity of the regional artisanal fleet, the analysis focused on a specific fleet segment defined by: (i) vessel size (8–10 m length, storage capacity <5 tonnes), (ii) crew size (≤5 individuals), (iii) fishing gear (gillnets), and (iv) trip duration (≤2 weeks). Data were derived from the Pará State Fishing Landings Monitoring System, collected through questionnaires between 2008 and 2010. Fishing profiles were identified using principal component analysis and hierarchical cluster analysis. Seven consistent profiles were distinguished, targeting acoupa weakfish (pescada amarela), megrim (pratiqueira), mullet (tainha), and multispecies assemblages. Additional profiles were associated with serra Spanish mackerel (serra) and king weakfish (pescada gó), recorded only in 2008 and 2010, and pacora weakfish (pescada curuca), recorded exclusively in 2010. This work represents the first multivariate approach to describe fishing profiles along the Eastern Amazon coast and provides novel insights into the organisation and dynamics of artisanal fisheries in the region.